Academic outcomes in a national afterschool program: The role of program experiences and youth sustained engagement. Issue 4 (2nd October 2022) - Seitz, Scot; Khatib, Nadim; Guessous, Omar; Kuperminc, Gabriel
Abstract: Researchers have documented positive associations among youth program quality and academic outcomes, primarily based on cross-sectional data. This study examined longitudinal associations among youth-reported program experiences and academic expectations, self-reported grades, and perceived value of school using data from the national evaluation of Boys and Girls Clubs of America (BGCA). The sample included 101, 050 Club attendees at 2, 741 BGCA sites throughout the United States from 2015-2018. Latent Growth Curve Modeling was used to examine change in youth-reported program experiences as well as the longitudinal associations among perceived program experiences and academic outcomes over time. Baseline perceptions of program experiences were associated prospectively with increased perceived value of school. In addition, gains in youth-reported program experiences predicted gains in each of the academic outcomes. These findings suggest that youth programs can promote positive academic trajectories when youth perceive the programs as continuing to meet their needs over time.